Professional prejudice: Are psychology and psychiatry helping or hindering our understanding of sexualities and gender? - Brouard, Pierre (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Tosh, Jemma (2015) Perverse psychology: The pathologization of sexual violence and transgenderism. London & New York: Routledge. ISBN 978-1-84872-173-9 pbk. Pages xiv + 146. South Africa is grappling with high levels of gender based violence and rape, some of it extreme in the lengths to which perpetrators go to assert dominance, mostly over women. Who can forget the horrific crime of rape, robbery and murder which took place at Rhodes Park in Johannesburg in October 2015, resulting in the recent sentencing of the perpetrators, all men? Please note this is a trigger warning for the next paragraph.